Comprehensive Chromosome Screening and Embryo Selection: Moving Toward Single Euploid Blastocyst Transfer - Forman, Eric J.; Hong, Kathleen H.; Treff, Nathan R.; Scott, Richard T. (Seminars in Reproductive Medicine, 2012)
Interest in using aneuploidy screening to select embryos has been renewed with the introduction of new methods for comprehensive chromosome screening (CCS) that evaluate all 24 chromosomes. With a series of experiments providing level I evidence of accuracy, reliability, safety, predictive value, and clinical efficacy, CCS-based selection of a single euploid blastocyst may provide an opportunity to finally realize the potential benefits and practical application of elective single embryo transfer. Furthermore, by incorporating CCS into research and development to control for chromosomal contribution to reproductive potential, additional biomarkers may now be more readily identified that help to further enhance the efficacy of embryo selection technology. This review describes the critical components of a valid CCS embryo selection methodology and discusses the limitations and opportunities for future routine application in reproductive medicine.
Keywords: comprehensive chromosome screening; preimplantation genetic screening; microarray; comparative genomic hybridization; single embryo transfer